A'uwẽ (Xavante) views of food security in a context of monetarization of an indigenous economy in Central Brazil. - James R Welch; Carlos E A Coimbra (PLoS ONE)
Following boom-and-bust economic cycles provoked by Brazilian governmental attempts to integrate Indigenous peoples into national society, it is approximately since the beginning of the 2000s that Brazilian Indigenous peoples came to be viewed officially as "poor" and victims of "hunger." Consequently, the national indigenist agency and other State entities started to conceive and implement diverse initiatives that ultimately injected money and resources into Indigenous communities. In 2019 we undertook an ethnographic study in three A'uwẽ (Xavante) communities in the Pimentel Barbosa Indigenous Reserve, Central Brazil, with the objective of analyzing how people understand and pursue food security. We propose that in the studied communities the complex network of A'uwẽ food reciprocity is a fundamental strategy for mitigating hunger and acute lack of food. We show that among the A'uwẽ, the hybrid economy that developed since the 1970s has proved resilient to dramatic transformations and uncertainty in the availability and characteristics of external government inputs.